LINKS BETWEEN LANGUAGE AND SOCIETY REVEALED THROUGH STUDYING TRANSLATION METHODS - O. R. Oksentyuk (Концепт: философия, религия, культура, 2019)
The article makes an attempt to summarize and develop the existing ways of classifying pragmatic adaptation (transcreation), while translating from one language into another. Such methods ensure that the receivers of information both in the source language and the language of translation can get similar messages both from the original and the translated text without having to overcome «transcultural barriers» that slow down and complicate comprehension. The analysis provides proof that there are correlations between such lines of research as sociolinguistics and pragmatic adaptation of translation (transcreation) because both of them have the same object of research. The researcher examines the currently used parameters of analyzing pragmatic adaptation and goes on to suggest looking at another possible level of adaptation, which takes into account the national variety of the language (if the language in question has several national varieties). To illustrate the need for this kind of approach the author provides examples from three versions of Anton Chekhov’s play «Three Sisters» prepared by British and American publishers as well as «Progress Publishers» (Moscow). The article also contains examples of why and how texts are adapted: 1) because the systems of languages are incompatible in many ways and at various levels and 2) because the realities of life (in a very broad sense of the word) are very diﬀerent, which defes easy adaptation.In conclusion the author suggests that further research into this feld is needed to develop more approaches to studying pragmatic adaptation.